2020
DOI: 10.1038/s41598-020-61852-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic effects of GM1 ganglioside, NGF, and FGF2 on canine dorsal root ganglia neurons in vitro

Abstract: certain growth factors 23. Gangliosides are sialic acid-containing glycosphingolipids that can be found in different cellular membranes. In the CNS gangliosides account for up to 10% of the total lipid content in neurons 24. They are involved in intercellular communication, cellular differentiation, neuronal development, and regeneration 25-28 due to their capacity to modulate Ca 2+ influx and their influence on the function of receptors for muscarinic acetylcholine, serotonin, glutamine, neurotransmitters, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 136 publications
0
11
0
Order By: Relevance
“…Based on the above research, this study further proved that GM1 combined with mild hypothermia treatment has a better protective efficacy on the neural function of neonates with HIE. The possible mechanism may be that the metabolic rate of brain tissues and cell energy are slowed down under mild hypothermia, which reduces neuron necrosis and apoptosis [ 23 ]. While low temperature environment alone cannot restore the damaged nerve cells, GM1, as an essential substance for the regeneration and development of brain nerves, can promote nerve regeneration [ 24 ], which makes up for the shortcomings of mild hypothermia therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above research, this study further proved that GM1 combined with mild hypothermia treatment has a better protective efficacy on the neural function of neonates with HIE. The possible mechanism may be that the metabolic rate of brain tissues and cell energy are slowed down under mild hypothermia, which reduces neuron necrosis and apoptosis [ 23 ]. While low temperature environment alone cannot restore the damaged nerve cells, GM1, as an essential substance for the regeneration and development of brain nerves, can promote nerve regeneration [ 24 ], which makes up for the shortcomings of mild hypothermia therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ganglioside-monosialic acid (GM1) is a monosialoglycosphingolipid mainly found in neurons and belongs to the family of gangliosides which are unique acidic glycolipids consisting of sphingosine, fatty acid, and sialic acid [8]. GM1 has been associated with essential functions in the processes of signal transduction, cell recognition, neurogenesis, and nerve development and differentiation [9][10][11]. In the 1980s, ganglioside treatment was found to be useful in the mitigation of vincristine-associated neuropathy, both in rabbit models and cancer patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GM1 elevates superoxide dismutase and glutathione levels to decrease anti-oxidant stress [42,43]. Animal studies showed that GM1 enhanced the activity of nerve growth factor, a protective factor of DRG [44]. To our knowledge, 3 studies (1 retrospective study and 2 randomised placebo-controlled trials) have evaluated the effectiveness of GM1 on chronic OIPN prevention [45À47].…”
Section: Introductionmentioning
confidence: 99%